2015
DOI: 10.1161/circheartfailure.114.002000
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Adverse Events During Continuous Flow Left Ventricular Assist Device Support

Abstract: Background-Adverse events (AEs), such as intracranial hemorrhage, thromboembolic event, and progressive aortic insufficiency, create substantial morbidity and mortality during continuous flow left ventricular assist device support yet their relation to blood pressure control is underexplored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 13 publications
(11 reference statements)
2
47
0
2
Order By: Relevance
“…In addition, similar to previous studies , we suspected that the “MAP” measured by Doppler and pulse oximeter is closer to the systolic arterial pressure (SAP) rather than the MAP when flow approaches pulsatile physiology. When patients were divided according to aortic valve opening (all of the time compared to none or every 2–3 beats), we indeed found that the resulting “MAP” according to Doppler and pulse oximeter correlated with the SAP ( r = 0.90 for Doppler and r = 0.91 for pulse oximeter) in patients with the aortic valve opening every beat.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, similar to previous studies , we suspected that the “MAP” measured by Doppler and pulse oximeter is closer to the systolic arterial pressure (SAP) rather than the MAP when flow approaches pulsatile physiology. When patients were divided according to aortic valve opening (all of the time compared to none or every 2–3 beats), we indeed found that the resulting “MAP” according to Doppler and pulse oximeter correlated with the SAP ( r = 0.90 for Doppler and r = 0.91 for pulse oximeter) in patients with the aortic valve opening every beat.…”
Section: Resultssupporting
confidence: 84%
“…Therefore, an important consideration in the noninvasive assessment of BP in an individual LVAD patient is the degree of aortic valve opening on the last echocardiogram. Despite this limitation, in a large study of Doppler derived BP in LVAD patients, a value of 90 mm Hg was associated with adverse events regardless whether this value reflected MAP or SAP .…”
Section: Discussionmentioning
confidence: 99%
“…Higher blood pressure has been associated with increases in intracranial hemorrhage, thromboembolic events, and progressive aortic insufficiency [15]. Unfortunately, the reduced pulse pressure during continuous-flow LVAD support limits our ability to accurately measure blood pressure with traditional oscillometric blood pressure cuffs, and Doppler opening blood pressure is commonly used as a surrogate of mean arterial pressure.…”
Section: Measuring Hemodynamics During Lvad Supportmentioning
confidence: 99%
“…Among them, stroke, bleeding, and right ventricular failure are the most common and serious. [6][7][8] Thus, BP control is paramount in managing VAD patients. 5 Previous clinical trials and observational studies have shown that poorly controlled blood pressure (BP) is strongly associated with stroke and other adverse events.…”
Section: Introductionmentioning
confidence: 99%